PTU-136 Does total number and positive lymph node ratio have an impact on outcome following surgical resection for hilar cholangiocarcinoma?. (28th May 2012) - Hakeem, A; Marangoni, G; Chapman, S; Young, R; Nair, A; Hidalgo, E; Toogood, G; Lodge, J P A; Prasad, K R
Abstract : Introduction: Lymph node status is an important predictor of survival following resection for hilar cholangiocarcinoma (HCCA). Controversies still exist regarding the extent of lymphadenectomy and whether an extended lymph node dissection improves outcome. This study aims to evaluate the prognostic value of the total number of nodes removed and positive lymphnode ratio (LNR) on overall and disease-free survival in patients undergoing resection for HCCA. Methods: From 1994 to 2010, 84 HCCA were resected at our Institution. Seventy-eight patients with available data were included in our analysis. Overall survival (OS) and disease-free survival (DFS) were calculated and stratified according to the number of lymph nodes excised and positive LNR at different cut-off levels. Results: An average of 13.8 lymph nodes were removed. 45 patients (57.7%) had a positive lymph node status, with a mean of 3.2 involved nodes per patient. 1, 5 and 10-year OS for N+ status was 60%, 10% and 10%, while N- OS was 82%, 41% and 41% (p=0.000). Similarly, 1, 5 and 10-year DFS was worse in the N+ group (71%, 45% and 42%) compared to N- (91%, 65% and 60%) (p=0.045). There was no difference in 1, 5 and 10-year OS (70%, 23%, 20% vs 70%, 23% and 20%, p=0.690) and DFS (78%, 48% and 48% v s 82%, 58% and 58%, p=0.305) when <10 nodes were removed (n=39) compared to ≥10 nodes (n=36). There was no difference in 1, 5 and 10-year OS (63%, 9% and 9% vs 60%, 10% and 10%, p=0.562) and DFS (78%, 40% and 40% vs 65%, 46% and 40%, p=0.795) when LNR <0.25 (n=22) was compared to LNR >0.25 (n=23). No difference was found when a cut-off of 15 total excised lymphnodes and LNR of 0.50 was used. Conclusion: The overall number of lymphnodes excised and positive LNR did not correlate with overall and DFS in resected HCCA. Larger, prospective studies are necessary to confirm these results. Competing interests: None declared.